Job Crafting in the Digital Workplace: A Systematic Literature Review Using the CIMO Framework - Syarifah Novieyana; Nur Afifah; Mustaruddin Mustaruddin; Titik Rosnani (Westscience Press, 2026)
Job crafting has become an increasingly important concept in human resource management and organizational behavior, particularly as employees face digital transformation, post-pandemic work arrangements, and uncertain organizational environments. Examining the historical background, interventions, processes, results, and potential future directions of job crafting research is the overarching goal of this study. This research assesses papers indexed in Scopus from 2020 to 2026 using a SLR technique, using the PRISMA procedure. A total of sixty-six articles made it into the review sample after going through the screening, identification, and eligibility procedures. The analysis was structured using the CIMO framework: Context, Intervention, Mechanism, and Outcome. The findings indicate that job crafting studies are predominantly conducted in service-based and public-oriented sectors, including hospitality, banking, technology, education, and public services. Most studies employ quantitative designs, particularly survey-based approaches and structural equation modeling. The Job Demands-Resources model, the theory of Conservation of Resources, and the theory of Self-Determination are the most prominent frameworks for understanding job crafting. Adaptability, inventiveness, job happiness, employee well-being, and productivity are the primary effects that have been recorded. However, the review also reveals several gaps, including the limited use of qualitative and longitudinal designs, insufficient attention to non-Western and developing-country contexts, and emerging concerns related to artificial intelligence, hybrid work, and over-crafting. This study contributes by offering an integrated CIMO-based synthesis and proposing future research directions for job crafting in digitally transforming workplaces.